IMPACT OF THE EXISTENCE OF PT. KML (KELOLA MINA LAUT) ON SOCIAL ECONOMIC CONDITIONS OF THE EAST LAMPUNG COMMUNITY - Buchori; misubargo; Dedi setiawan (PT. Berkah Digital Teknologi, 2022)
Purpose of the study — To find out and analyze whether there is an impact on the existence of PT. KML (Manage Mina Laut) on the socio-economic conditions of the people of Labuhan Maringgai Village, Labuhan Maringgai District, East Lampung. Research method— This type of research is classified as qualitative research. Researchers tried to collect data through interviews and observations by going directly to the field to meet informants, namely the people of Labuhan Maringgai as many as 100 respondents. Result—The impact of the existence of PT. KML (Manage Mina Laut) on the socio-economic conditions of the people of Labuhan Maringgai, in terms of social conditions, has not yet been felt by the community. In addition, it is known that there is an influence on the economic conditions around PT KML because seen from the income of the community before and after the existence of the company, it shows that there is an increase in income after the existence of PT KML in Maringgai Harbor. Conclusion— Socially PT. KML (Manage Mina Laut) does not affect the surrounding community, but in terms of income, PT. KML (Manage Mina Laut) has an effect on the surrounding community.